Osteogenesis ability of CAD/CAM porous zirconia scaffolds enriched with nano-hydroxyapatite particles - Moustafa N. Aboushelib; Rehab Shawky (SpringerOpen, 2017)
Abstract Background The aim of this study was to evaluate osteogenesis ability of CAD/CAM porous zirconia scaffolds enriched with hydroxy apatite used to augment large boney defects in a dog model. Methods Surgical defects were made bilaterally on the lower jaw of 12 Beagle dogs. Cone beam CT images were used to create three dimensional images of the healed defects. Porous zirconia scaffolds were fabricated by milling custom made CAD/CAM blocks into the desired shape. After sintering, the pores of half of the scaffolds were filled with a nano-hydroxy apatite (HA) powder while the other half served as control. The scaffolds were inserted bilaterally in the healed mandibular jaw defects and were secured in position by resorbable fixation screws. After a healing time of 6 weeks, bone-scaffold interface was subjected to histomorphometric analysis to detect the amount of new bone formation. Stained histological sections were analyzed using a computer software (n=12, α=0.05). Mercury porosimetery was used to measure pore sizes, chemical composition was analyzed using energy dispersive x-ray analysis (EDX), and the crystal structure was identified using x-ray diffraction micro-analysis (XRD). Results HA enriched zirconia scaffolds revealed significantly higher volume of new bone formation (33% ± 14) compared to the controls (21% ± 11). New bone deposition started by coating the pore cavity walls and proceeded by filling the entire pore volume. Bone in-growth started from the surface of the scaffold and propagated towards the scaffold core. Islands of entrapped hydroxy apatite particles were observed in mineralized bone matrix. Conclusions Within the limitations of this study, hydroxy apatite enhanced osteogenesis ability of porous zirconia scaffolds.